Enhanced inflammasome activation and reduced sphingosine-1 phosphate S1P signalling in a respiratory mucoobstructive disease model - Hai B. Tran; Matthew G. Macowan; Adrian Abdo; Martin Donnelley; David Parsons; Sandra Hodge (BMC, 2020)
Abstract Background Inflammasomes and sphingosine-1-phosphate (S1P) signalling are increasingly subject to intensive research in human diseases. We hypothesize that in respiratory muco-obstructive diseases, mucus obstruction enhances NLRP3 inflammasome activation and dysregulated S1P signalling. Methods Lung tissues from mice overexpressing the beta-unit of the epithelial sodium channel (βENaC) and their littermate controls were examined by histology, immunofluorescence and confocal microscopy, followed by ImageJ quantitative analysis. Results Lower airways in βENaC mice showed patchy patterns of mucus obstruction and neutrophil-dominant infiltrations. In contrast to a ubiquitous distribution of TNFα specks, significantly (p < 0.05) increased specks of bronchiolar NLRP3, IL-1β, and IgG in the βENaC mouse lungs were localized to the vicinity of mucus obstruction sites. Bright Spinster homologue 2 (SPNS2) at the epithelial apex and positive correlation with sphingosine kinase 1 (SPHK1) (R2 = 0.640; p < 0.001) supported the normal bronchial epithelium as an active generator of extracellular S1P. SPNS2 in βENaC mice was sharply reduced (38%, p < 0.05) and lost apical localization at sites of mucus obstruction. A significant (34%; p < 0.01) decrease in epithelial SPHK2 was also noted at mucus obstruction sites. Conclusion These results support that mucus obstruction may enhance NLRP3 inflammasome activation and dysregulated S1P signaling.